How well are environmental attitudes and sustainable transport alternatives aligned in Santiago de los Caballeros (Dominican Republic) - Indelicato, Alessandro; Moral-Cuadra, Salvador; Orgaz-Agüera, Francisco; Martín, Juan Carlos (International Journal of Sustainable Transportation, 2025)
This study analyses Environmental Attitudes (EA) and preferences for Sustainable Transport Alternatives (STA) among residents of Santiago de los Caballeros, Dominican Republic. Using survey data from 600 participants aged 18 and older, stratified by socioeconomic characteristics, the research employs the Fuzzy Hybrid TOPSIS method to assess EA and STA based on these factors. Additionally, the Fuzzy Clustering ECO-Extended Apostle Model identifies four categories of individuals: Environmental Consistent, Environmental Conscientious, Environmental Inconsistent, and Environmental Negationist. Probability Conditional Ratios highlight the likelihood of individuals falling into these categories. Results reveal substantial socioeconomic differences in EA and STA, with women and those with primary education showing strong preferences for sustainable transport. However, these preferences may be influenced by socioeconomic constraints rather than solely by environmental awareness. The findings highlight the intricate relationship between socioeconomic conditions and sustainable attitudes, offering valuable insights into targeted policy strategies for promoting sustainable transportation in diverse populations.
Keywords: Dominican Republic; environmental attitudes; fuzzy clustering ECO-extended apostle model; sustainable transport alternatives